Aproximación conceptual de las competencias en el contexto educativo (2018)
The concept of competences has been transferred from the business field to educational institutions, mainly towards higher education, which seeks quality educational processes in opposition to the traditionally established models based on the transmission of information, focused on the teacher and his knowledge, with little active student participation. However, in the academic environment, a series of concepts about competences have been established that generate misunderstandings of the term. In this sense, we propose a conceptual approach and some reflections on the development of the competency-based approach in the educational institution.